Taxas de sobrevivência de participantes de fundos de pensão vinculados ao setor elétrico nacional - Santos, Marcos Antonio de Lima (2011)
This paper aims to calculate the survival rates of the participants of the Pension Funds electricity sector as well as finding the parametric survival model that best represents the data in the study. For development work we used data from 14 organizations with information of participants and retirees, with the exception of the disabled, for the period 2001 to 2009, amounting to a total of 100,000 lives analyzed. To calculate the crude rates of survival using the indirect method described in Ferreira (1985). After calculation of the original rates, we make the process of smoothing by moving averages in order to correct the unwanted fluctuations in the curve obtained crude survival. Even after the smoothing process, we chose to restrict the study to age within the range of 25 to 85 years, given the low number of deaths at ages above and exposed. From the smooth curve we apply the parametric models of survival Gompertz, Gompertz-Makeham, Thiele and Helingman-Pollard, to test the best fit of the equation. The results showed that none of the models proved to be analyzed with parametric statistical robust enough to conduct a predictive analysis with acceptable reliability.